2004
DOI: 10.1128/aem.70.5.3122-3129.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and In Situ Detection of a Novel Chemolithoautotrophic Sulfur-Oxidizing Bacterium in Wastewater Biofilms Growing under Microaerophilic Conditions

Abstract: We successfully isolated a novel aerobic chemolithotrophic sulfur-oxidizing bacterium, designated strain SO07, from wastewater biofilms growing under microaerophilic conditions. For isolation, the use of elemental sulfur (S 0 ), which is the most abundant sulfur pool in the wastewater biofilms, as the electron donor was an effective measure to establish an enrichment culture of strain SO07 and further isolation. 16S rRNA gene sequence analysis revealed that newly isolated strain SO07 was affiliated with member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…This result suggested that the novel SOB strain SO07 could be responsible for oxidation of S 0 to SO 4 2Ϫ under oxic conditions. Further isolation and characterization of strain SO07 revealed that strain SO07 was an aerobic chemolithoautotrophic sulfur-oxidizing bacterium capable of oxidizing S 0 and H 2 S to SO 4 2Ϫ (13). More details concerning the ecophysiological characteristics of strain SO07 have been reported previously (13).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that the novel SOB strain SO07 could be responsible for oxidation of S 0 to SO 4 2Ϫ under oxic conditions. Further isolation and characterization of strain SO07 revealed that strain SO07 was an aerobic chemolithoautotrophic sulfur-oxidizing bacterium capable of oxidizing S 0 and H 2 S to SO 4 2Ϫ (13). More details concerning the ecophysiological characteristics of strain SO07 have been reported previously (13).…”
Section: Discussionmentioning
confidence: 99%
“…Related isolates include the sulfur-oxidizing lithoautotrophs "Ca. Thiobacillus baregensis" (25,26), Thiofaba tepidiphila (42), and Thiovirga sulfuroxydans (29,30). Representatives of the clade defined by these isolates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of S 0 as an electron donor was an effective measure to establish an enrichment culture of strain SO07 T and for further purification (Ito et al, 2004). The 16S rRNA genes of large numbers of uncultured bacterial clones that are closely related to strain SO07 T have been found in GenBank (Benson et al, 2003), suggesting the widespread distribution and ecological importance of these types of bacteria in the environment.…”
mentioning
confidence: 99%
“…The composition of SOB medium (in g l 21 ) was KH 2 PO 4 (0?5), K 2 HPO 4 (0?5), NH 4 Cl (0?5), MgSO 4 .7H 2 O (0?1), CaCl 2 (0?05) and NaHCO 3 (1?0), plus 1 ml trace element solution l 21 (Kuenen et al, 1991). The procedures for enrichment and isolation have been described previously (Ito et al, 2004). Cells grown in liquid SOB medium with thiosulfate (6?5 mM) as a sole electron donor were used for studies on phenotypic properties and chemotaxonomic traits unless otherwise specified.…”
mentioning
confidence: 99%
See 1 more Smart Citation